Biblionline Vol. 8, n. especial (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Biblionline Vol. 8, n. especial (2012)Link de acesso ao númerohttp://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1131/showToc